2016
DOI: 10.1021/acs.nanolett.6b01595
|View full text |Cite
|
Sign up to set email alerts
|

Large Magnetoresistance in Single-Radical Molecular Junctions

Abstract: Organic radicals are promising building blocks for molecular spintronics. Little is known about the role of unpaired electrons for electron transport at the single-molecule level. Here, we examine the impact of magnetic fields on electron transport in single oligo(p-phenyleneethynylene) (OPE)-based radical molecular junctions, which are formed with a mechanically controllable break-junction technique at a low temperature of 4.2 K. Surprisingly huge positive magnetoresistances (MRs) of 16 to 287% are visible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
118
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 56 publications
(84 reference statements)
5
118
0
Order By: Relevance
“…An experimental verification of this predictions, as well as of a magnetic transition at κ ≈ 0.025 (for ν = 4/11), will serve as nontrivial confirmations of the physics described above. The spin polarizations and spin phase transitions at ν = n/(2pn±1) have been measured by transport [25][26][27][28][29][30], optical [31][32][33][34], NMR [35][36][37][38][39], and compressibility [40] measurements; analogous valley polarization transitions have been observed in AlAs quantum wells [41][42][43]; and the experimental observations are generally consistent with the CF theory [24,44].…”
Section: /11mentioning
confidence: 99%
“…An experimental verification of this predictions, as well as of a magnetic transition at κ ≈ 0.025 (for ν = 4/11), will serve as nontrivial confirmations of the physics described above. The spin polarizations and spin phase transitions at ν = n/(2pn±1) have been measured by transport [25][26][27][28][29][30], optical [31][32][33][34], NMR [35][36][37][38][39], and compressibility [40] measurements; analogous valley polarization transitions have been observed in AlAs quantum wells [41][42][43]; and the experimental observations are generally consistent with the CF theory [24,44].…”
Section: /11mentioning
confidence: 99%
“…The [0,0] magnetic configuration means that the two ZGNR electrodes both are anti-ferromagnetic and in ground state if there is no applied magnetic field. The [1,1] magnetic configuration means that the magnetization of the two ZGNR electrodes are parallel by applying a homogeneous magnetic field across the device [32, 33]. …”
Section: Resultsmentioning
confidence: 99%
“…

We studied the single-molecule conductance through an acid oxidant triggered phenothiazine (PTZ-) based radical junction using the mechanically controllable break junction technique.T he electrical conductance of the radical state was enhanced by up to 200 times compared to the neutral state,with high stability lasting for at least two months and high junction formation probability at room-temperature.T heoretical studies revealed that the conductance increase is due to asignificant decrease of the HOMO-LUMO gap and also the enhanced transmission close to the HOMO orbital when the radical forms.T he large conductance enhancement induced by the formation of the stable PTZ radical molecule will lead to promising applications in single-molecule electronics and spintronics.

Investigations of charge transport through single molecules provide vital information for the design of materials for nextgeneration electronic devices. [5] However, although some pioneering studies investigated the charge transport through radicals using molecular assemblies [5a, 6] or under ultrahigh vacuum and cryogenic environment, [3b,5b] the seeking of appropriate molecular radicals for the fabrication of stable and highly conductive single-molecule devices remained as amajor challenge for applying molecular radicals for future electronics devices.Thep henothiazine (PTZ) system can undergo oneelectron oxidation on the nitrogen atom to form ar adical cation (PTZ + C) [7] with accompanying significant color change in solution by adding acid oxidant such as trifluoroacetic acid (TFA) under ambient conditions.M ore interestingly,t he butterfly structure of the PTZ became more planar for the radical cation with electron density delocalized over the whole molecule including the central ring. [5] However, although some pioneering studies investigated the charge transport through radicals using molecular assemblies [5a, 6] or under ultrahigh vacuum and cryogenic environment, [3b,5b] the seeking of appropriate molecular radicals for the fabrication of stable and highly conductive single-molecule devices remained as amajor challenge for applying molecular radicals for future electronics devices.

Thep henothiazine (PTZ) system can undergo oneelectron oxidation on the nitrogen atom to form ar adical cation (PTZ + C) [7] with accompanying significant color change in solution by adding acid oxidant such as trifluoroacetic acid (TFA) under ambient conditions.M ore interestingly,t he butterfly structure of the PTZ became more planar for the radical cation with electron density delocalized over the whole molecule including the central ring.

…”
mentioning
confidence: 99%
“…[1] Recently,a ll-organic radical species have raised broad interests as the unpaired electron can lead to novel quantum phenomena for tuning the electronics properties, [2] such as Kondo effects, [3] quantum interference [4] and magnetoresistive effects. [5] However, although some pioneering studies investigated the charge transport through radicals using molecular assemblies [5a, 6] or under ultrahigh vacuum and cryogenic environment, [3b,5b] the seeking of appropriate molecular radicals for the fabrication of stable and highly conductive single-molecule devices remained as amajor challenge for applying molecular radicals for future electronics devices.Thep henothiazine (PTZ) system can undergo oneelectron oxidation on the nitrogen atom to form ar adical cation (PTZ + C) [7] with accompanying significant color change in solution by adding acid oxidant such as trifluoroacetic acid (TFA) under ambient conditions.M ore interestingly,t he butterfly structure of the PTZ became more planar for the radical cation with electron density delocalized over the whole molecule including the central ring. [8] Such prominent changes in the electronic properties of the PTZ radicals have received increasing research interests in organic light-emitting diodes, [9] and also offer promising applications in the radical-based molecular electronics devices.Herein, we study the single-molecule conductance of aP TZ derivative and its corresponding radical cation using the mechanically controllable break junction (MCBJ) technique [10] in am ixed tetrahydrofuran/1,3,5-trimethylbenzene (THF/TMB,1:4 v/v)solution at room temperature,asshown in Scheme 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation